Pengaruh Motivasi dan Lingkungan Kerja terhadap Kinerja Pegawai di BPJS Kesehatan Cabang Sumedang - Setiawan, Indra; Pratminingsih, Sri Astuti (Prodi Manajemen, Fakultas Ekonomi, Universitas Pamulang, 2024)
Employee performance is one of the most important aspects in the company. An employee's performance is influenced by several factors, including motivation and work environment Based on the background of the problem, this study aims to find out the condition and influence of motivation and work environment on employee performance. The method used in this study is a verifiable descriptive method with a sample of 68 people. The results of the study showed that: 1) Motivation had a positive and significant effect on the performance of BPJS Kesehatan Sumedang Branch employees. This means that the better the motivation of employees, the higher the performance of employees. 2) The work environment has a positive and significant effect on the performance of BPJS Kesehatan Sumedang Branch employees, which is 38.2%. This means that the better the work environment is created, the better the performance of employees will increase. 3) Motivation and work environment have a positive and significant effect on the performance of BPJS Kesehatan Sumedang Branch employees, which is 30.6%. This means that the better the motivation and work environment, the better the performance of BPJS Kesehatan Sumedang Branch employees